Human papillomavirus disease in GATA2 deficiency: a genetic predisposition to HPV-associated female anogenital malignancy - Dancy, Ehren; Stratton, Pamela; Pichard, Dominique C.; Marciano, Beatriz E.; Cowen, Edward W.; McBride, Alison A.; Van Doorslaer, Koenraad; Merideth, Melissa A.; Salmeri, Noemi; Hughes, Marybeth S.; Heller, Theo; Parta, Mark; et al. (Frontiers in Immunology, 2024)
Objective: Patients with pathogenic variants in the GATA Binding Protein 2 (GATA2), a hematopoietic transcription factor, are at risk for human papillomavirus-related (HPV) anogenital cancer at younger than expected ages. A female cohort with GATA2 haploinsufficiency was systematically assessed by two gynecologists to characterize the extent and severity of anogenital HPV disease, which was also compared with affected males.Methods: A 17-year retrospective review of medical records, including laboratory, histopathology and cytopathology records was performed for patients diagnosed with GATA2 haploinsufficiency followed at the National Institutes of Health. Student's t-test and Mann-Whitney U test or Fisher's exact test were used to compare differences in continuous or categorical variables, respectively. Spearman's rho coefficient was employed for correlations.Results: Of 68 patients with GATA2 haploinsufficiency, HPV disease was the initial manifestation in 27 (40%). HPV occurred at median 18.9 (15.2-26.2) years in females, and 25.6 (23.4-26.9) years in males.Fifty-two (76%), 27 females and 25 males, developed HPV-related squamous intraepithelial lesions (SIL) including two males with oral cancer. Twenty-one patients developed anogenital high-grade SIL (HSIL) or carcinoma (16 females versus 5 males, (59% versus 20%, respectively, p=0.005) at median 27 (18.6-59.3) years for females and 33 (16.5-40.1) years for males. Females were more likely than males to require >2 surgeries to treat recurrent HSIL (p=0.0009). Of 30 patients undergoing hematopoietic stem cell transplant (HSCT) to manage disease arising from GATA2 haploinsufficiency, 12 (nine females, three males) had persistent HSIL/HPV disease. Of these nine females, eight underwent peri-transplant surgical treatment of HSIL. Five of seven who survived post-HSCT received HPV vaccination and had no or minimal evidence of HPV disease 2 years post-HSCT. HPV disease persisted in two receiving immunosuppression. HPV disease/low SIL (LSIL) resolved in all three males.Females with GATA2 haploinsufficiency exhibit a heightened risk of recurrent, multifocal anogenital HSIL requiring frequent surveillance and multiple treatments. GATA2 haploinsufficiency must be considered in a female with extensive, multifocal genital HSIL unresponsive to multiple surgeries. This population may benefit from early intervention like HSCT accompanied by continued, enhanced surveillance and treatment by gynecologic oncologists and gynecologists in those with anogenital HPV disease.